Phytochemical composition and antioxidant activity of Cinnamomum burmannii Blume extracts and their potential application in white chocolate - Muhammad, Dimas Rahadian Aji; Tuenter, Emmy; Patria, Graha Darma; Foubert, Kenn; Pieters, Luc; Dewettinck, Koen (Food chemistry, 2021)
•C. burmannii extracts contained various phenolic compounds.•The effect of the different extraction method was revealed.•Cryo-SEM analysis showed the cavitation effect of ultrasonic extraction.•Significant improvement on the antioxidant activity of white chocolate was found. This study aims at determining the potentials of cinnamon (Cinnamomun burmannii) extracts to improve the health-promoting properties of white chocolate. LC-HRMS analysis was employed to obtain information regarding the phytochemical content while the phosphomolybdenum, FRAP and DPPH assays were used to determine antioxidant activity of cinnamon extract. Furthermore, the cinnamon extract was loaded into nanoparticles before adding it to white chocolate. The results show that cinnamon extracts contained phenols up to 310 mg EE and possessed antioxidant activity up to 260 mg TAE per gram of dry extract depending on the extraction mode (i.e., traditional and ultrasonic-assisted method) and the solvent type. The cinnamon extract contained catechin, epicatechin, procyanidin B2, quercitrin, 3,4-dihydroxybenzaldehyde, protocatechuic acid and cinnamic acid at levels of 51, 53, 1396, 13, 1138, 228 and 934 µg/g of dry extract, respectively. The encapsulated cinnamon extract increased the phenolic content of white chocolate from 47.6 to 1060.6 µg EE/g.